Impact of concentric muscle failure on high and low intensity resistance training in hypertrophy programs: A systematic review (Research, Society and Development, 2023)
Introduction: Resistance training is well established as a primary strategy based on resistance exercise in producing increased muscle mass in humans. Objectives: Investigate the effects of concentric muscle failure in high and low intensity resistance training in programs aimed at hypertrophy. Methods: The type of study to be carried out in the present work was a systematic review, where careful attention was paid to the following steps: formulation of the guiding question; selection of studies based on year of publication and title; selection of studies by their abstracts and selection by the full text; and subsequently, extraction of data from the included studies; evaluation and interpretation of results and, finally, presentation of the review of the knowledge produced. Results. Discussion: diversity of conclusions in the compared studies highlights the complexity of the influence of muscle failure on resistance training. These differences can be attributed to a series of variables, such as intensity, population studied and training methodology. Therefore, the decision to incorporate muscle failure into a training program should be made by carefully considering the context and individual goals of the practitioner, considering the insights provided by these studies. Conclusion: this review presents comprehensive analyzes of the effects of concentric muscle failure in resistance training, considering a variety of methodological designs studied. Thus, we highlight the complex relationship between muscle failure and the equalization between volume and intensity of resistance training.